Stories about Animals: with Pictures to Match - Woodworth, Francis C. (Francis Channing), 1812-1859 (Salt Lake City, UT : Project Gutenberg, 2006)
"Stories About Animals: with Pictures to Match" by Francis C. Woodworth is a collection of animal stories written in the mid-19th century. The book focuses on anecdotes that highlight the intelligence, habits, and emotional bonds of various animals, particularly quadrupeds, aimed at entertaining and educating young readers. At the start of the book, the author introduces his intention behind compiling these animal anecdotes, explaining that the stories are selected to be lively and engaging rather than scientific. He emphasizes the extraordinary qualities and loyalty of animals, particularly dogs, as seen through the tale of a faithful dog mourning his deceased master and another saving a child from drowning. These narratives serve both to amuse the reader and instill values of empathy, courage, and appreciation for the animal kingdom, setting a foundation for the stories that will follow. (This is an automatically generated summary.)
Release date is 2006-07-06
E-text prepared by Ben Beasley, Paul Ereaut, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Animal behavior; Animals -- Folklore